GEOMETRY LEARNING BASED ON THE ETHNOMATHEMATICS METAVERSE OF TUGU JOGJA TO DEVELOP STUDENTS' COGNITIVE LEVELS - Ihsan Annafi Azhar; Muhammad Al-Jabbar; Priyambodo (Ethnomathematics Journal, 2025)
This study focused on analyzing the implementation of metaverse-based ethnomathematics in geometry learning for 9th-grade junior high school students. The aim of this research is to explore the concept of three-dimensional shapes in the Tugu Jogja monument as part of local culture using metaverse technology. The study sought to enhance the cognitive level of 9th-grade students in understanding the concepts of solid geometry, including both flat and curved surfaces, with the metaverse centered on Tugu Jogja. The method employed is purposive sampling, involving 29 ninth-grade students, with pre-tests and post-tests administered to measure the improvement in students’ cognitive levels. The data analysis results show a significant difference in students’ understanding after applying this approach, with a p-value of 0.00019 < 0.05. This proves that metaverse-based ethnomathematics geometry learning is effective in developing the cognitive levels of 9th-grade students. The exploration of Tugu Jogja through the metaverse medium contains mathematical elements such as flat-sided and curved-sided three-dimensional shapes. Through this learning media, it is possible to develop innovative learning methods that integrate technology and local culture to create more interactive and meaningful learning experiences.